Relationship between entry grades and attrition trends in the context of higher education: Implication for open innovation of education policy - Jacob Cherian; Jolly Jacob; Rubina Qureshi; Vilas Gaikar (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Student retention has emerged as a significant and expensive challenge for higher education institutes worldwide. Although several studies have been conducted on increasing student numbers and diversity in higher education institutes, studies on the relationship between student retention and entry grades are limited, particularly in the UK. The aim of this paper was to examine the relationship between entry grades and student attrition in the context of higher education in the UK. A quantitative methodology was used in this study, wherein data were derived from secondary sources, including University and Colleges Admissions Service (UCAS) tariff points and full- and part-time undergraduate student enrolment between 2012 and 2017. The data were extracted and analyzed using Higher Education Statistics Agency (HESA) performance indicators. The findings indicate that there exists a clear association between entry grades and student retention for part-time students, which may aid policy makers, academics, university staff, and higher education stakeholders to develop appropriate strategies to address attrition levels.
Keywords: 650; entry grades; HESA performance indicators; higher education; stakeholders; student retention